Biofiltro aerado submerso preenchido com Biobob® aplicado ao tratamento de efluente de campus universitário - Martins, Pedro Mouco (2014)
Improper disposal of effluents undertakes water quality and cause damage to the environment . The Higher Education Institutions can be potentially polluting because they generate effluents from many different areas of functioning. In this paper we evaluate the performance of a submerged aerated biofilter (SAB) filled with Biobob ® used to treat effluent from the UTFPR - Londrina. In the system the air was injected into the SAB by means of an aquarium pump type and the recirculation of the effluent was performed by washing machine pump. The amount of injected air was controlled by a flowmeter and an aerator, while recirculation by a tap. The SAB operated in batch with 12-hour time cycle, with sampling at the end of this period. The effects of air flow (Qair) and recirculation flow sewage (Qsewage) on the removal of Chemical Oxygen Demand (COD) and ammonia nitrogen were investigated. 12 laboratory tests were performed which followed a statistical statistical planning of a central composite design (CCD), the independent variables were between 0.2 and 0.6 L.min -1 to Qair and from 2 to 6 L.min -1 to Qsewage. For COD, from the statistical analysis of the results by analyzing the effects of the independent variables to the response variable removal of gross COD, with significance level of 10%, a mathematical model and boundary curve was generated. Linear and quadratic Qsewage parameters were significant, besides the interaction Qair and Qsewage. The quadratic regression model for COD removal had adjusted R2 equal to 0.64, with confidence level of 90%. For ammonia, with p-value <0.1, the values of studied groups was not possible to make statistical inference, obtaining model and contour curves. The system showed removal efficiency of ammonia-N between 60 and 70% and an average volumetric nitrification of 0.01704 kgN.m-³.day-¹.